Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

N-substitution of polybenzimidazoles: synthesis and evaluation of physical properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (European Polymer Journal, 2009)
Series of N-substituted polybenzimidazoles (PBI) were synthesized using selective alkyl groups with varying bulk and flexibility, viz., methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. PBl-I based on 3,3'-diaminobenzidine (DAB) and isophthalic acid and PBI-Bul based on DAB and 5-tert-butyl isophthalic acid were chosen for N-substitution. Structural characterizations of substituted polymers by FT-IR and (1)H NMR revealed elimination of hydrogen bonding. Evaluation of their physical properties revealed that N-substitution rendered better solvent solubility in common organic solvents, more open polymer matrix, but reduced thermal properties in comparison to their respective parent PBI. 4-tert-butylbenzyl, methylene trimethylsilane or n-butyl group substituted polymers were soluble even in chlorinated solvents (CHCl(3) and TCE). Substantial variations in gas permeability of inert gases, He and Ar and attractive P(He)/P(Ar) selectivity, especially after methyl group substitution depicted potential of these materials for gas separation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; hydrogen bonding; N-Substitution; Polybenzimidazole

Polybenzimidazoles tethered with N-Phenyl 1,2,4-triazole units as polymer electrolytes for fuel cells - Potrekar, R. A.; Kulkarni, M. P.; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Polybenzimidazole (PBI) polymers tethered with N-phenyl 1,2,4-triazole (NPT) groups were prepared from a newly synthesized aromatic diacid, 3'-(4-phenyl-4H-1,2,4-triazole-3,5-diyl) dibenzoic acid (PTDBA). The obtained polymers show superior thermal and chemical stability and good solubility in many aprotic solvents. The inherent viscosities of all polymers were around 1 dL/g. They exhibit high thermal stability with initial decomposition temperature ranging from 515 to 530 degrees C, high glass transition temperature ranging from 375 to 410 degrees C, and good mechanical properties with tensile stress in the range of 66-98 MPa and modulus 1897-2600 MPa. XRD analysis indicates that these polymers are amorphous in nature. PhysicochemiCal properties such as water and phosphoric acid-uptake, oxidative stability, and proton conductivity of membranes of these polymers have also been determined. The proton conductivity ranged from 4.7 x 10(-3) to 1.8 x 10(-2) S cm(-1) at 175 degrees C in dry conditions. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2289-2303, 2009
Keywords: fuel cells; Polybenzimidazole; synthesis and characterization; Triazole

Variation in acid moiety of polybenzimidazoles: investigation of physico-chemical properties towards their applicability as proton exchange and gas separation membrane materials - Kumbharkar, S. C.; Islam, Md. Nazrul; Potrekar, R. A.; Kharul, Ulhas K. (Polymer, 2009)
A series of polybenzimidazoles (PBIs) were prepared from 3,3'-diaminobenzidine (DAB) and substituted aromatic dicarboxylic acids. Effects of added polarity, bulk and isomerism in the dicarboxylic acid moiety on the properties of formed aromatic polybenzimidazoles were investigated. Solution polycondensation procedure was optimized for individual case of PBI synthesis in order to obtain inherent viscosity of >= 1 dL/g. Analysis of physical properties, water uptake, acid doping (H(3)PO(4) and H(2)SO(4)) and gas permeability was performed. All these PBIs exhibited high thermal stability, good solvent solubility and amorphous nature. The uptake of H(3)PO(4) varied from 9 to 20.1 moles per repeat unit (mol/RU), H(2)SO(4) uptake varied from 3.39 to 3.81 mol/RU, while water uptake varied from 1.8 to 3.6 mol/RU of PBI. The dibromoterephthalic acid and tert-butylisophthalic acid based PBI showed the highest H(3)PO(4) uptake in the series, while tert-butylisophthalic acid based PBI exhibited the highest water uptake. Acid uptake was correlated with swelling of the PBI matrix, while density estimation of H(3)PO(4)-doped PBI by He gas expansion method could be correlated to the physical state of PBI. 5-tert-Butylisophthalic acid and 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) based PBI exhibited higher H(2) and O(2) permeability than other PBIs. The ideal gas selectivity for O(2)/H(2) was considerably higher for most of the PBIs than conventional gas separation membrane materials. These analyses suggested that some of these PBIs have a potential to be used as a PEM or gas separation membrane material. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeability; Polybenzimidazole; Proton exchange membrane

Investigation of gas permeation properties of systematically modified polybenzimidazoles by N-substitution - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Gas permeation behavior of a series of thermally stable N-substituted polybenzimidazoles by systematically varying bulk and flexibility of the substituent was investigated. Two different PBIs having variation in their acid moiety, viz., PBI-I (based on isophthalic acid) and PBI-BuI (based on 5-tert-butyl isophthalic acid) were selected for N-substitution by alkyl groups possessing different bulk and flexibility. These substituent groups were methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. Pure gas sorption and permeability using H(2), N(2), O(2), CH(4) and CO(2) were investigated and correlated with physical properties of formed polymers. Estimation of dual-mode sorption parameters, coefficients of sorption, permeability and diffusion for different gases provided an insight towards effects of nature of a substituent group and parent PBI on governing gas sorption and permeation properties. By changing the substituent group, diffusivity coefficients was found to vary to a larger extent than the solubility coefficient. This significantly enhanced gas permeability for different gases by 1.2-129 times than that of parent PBIs. The permselectivity P(O2)/P(N2) was increased (up to 237%), while for other gas pairs, it was decreased to a different extent. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; N-Substitution; Polybenzimidazole; Sorption

Transport of inorganic acids through polybenzimidazole (PBI) based membranes by chemo-dialysis - Chendake, Yogesh J.; Kharul, Ulhas K. (Desalination and Water Treatment, 2012)
A process of chemo-dialysis involving poly(benzimidazole) (PBI) as a chemically active membrane material is proposed for the transport of inorganic acids. These membranes possessing basic nature selectively bind acid molecules present in the feed solution due to acid-base interactions. They are transported across the membrane by concentration gradient as the driving force. The transported acid molecules are stripped away from other side of the membrane surface by a suitable stripping agent or water. Effects of nature of feed acid (pK(a), molecular size), its concentration in the feed solution and the nature of stripping agent (base or water) on acid transport properties are presented. Membranes showed appreciable transport rates for three acids, viz., H2SO4, HCl and HNO3. The fluxes for different acids varied from 16.1 to 140.7 g/m(2) h under different operating conditions. Most significantly, there was no transport of non-acidic solutes such as NaCl or glucose. This could be made possible since these solutes neither get sorbed in the membrane matrix, nor does the membrane exhibit any porosity for the transport to occur through pores. This resulted in practically infinite selectivity of transported acid over the non-acidic solutes. Use of water as the stripping agent allows recycling of the acid, making the process economically attractive. Moreover, possible recovery of acid and its reuse eliminated the requirement of acid neutralization and disposal; which is a routine practice followed today. Thus, this process of chemo-dialysis is economically attractive and environmentally benign.
Keywords: Acid transport; Chemical interaction; Chemo-dialysis; Inorganic acids; Membrane; Polybenzimidazole

Investigation of gas permeation properties of film forming polymeric ionic liquids (PILs) based on polybenzimidazoles - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2014)
Polymeric ionic liquids (PILs) are emerging as new generation membrane materials for CO2 separation. Gas permeation properties of a recently developed PIL family based on three structurally different polybenzimidazoles (PBIs) possessing excellent film forming characteristics are reported. Effects of cationic backbone and anions on gas permeation properties of PILs using pure gases (He, H-2, N-2, CH4, and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. In comparison to the parent PBIs, PILs exhibited generally higher CO2 permeability, without largely affecting CO2 based selectivity. Some of these PILs exhibiting high PCO2/PCH4, selectivity and P-H2/P-CO2, approaching similar to 1 indicated dominance of CO2 sorption over diffusion. The CO2 sorption specificity of these PILs was distinctly observed based on their improved S-CO2/S-N2, S-CO2/S-CH4 and S-CO2/S-H2 selectivity than their parent PBIs. A large variation in permeation properties of PILs based on a common polycation but different anions indicated that anions play a crucial role on governing gas permeation properties of these PILs. (C) 2014 Elsevier B.V. All rights reserved
Keywords: Gas permeation; Membranes for CO2 separation; Polybenzimidazole; Polymeric ionic liquid

PBI-BuI and PAN-PSSALi based UF membranes: effects of solute and membrane surface interactions on rejection and flux - Bhagat, Deepti G.; Mule, Bhavana; Mandlekar, Neeraj; Pandare, Kiran; Kharul, Ulhas K. (Desalination, 2014)
Ultrafiltration membrane using tert-butylpolybenzimidazole (PBI-BuI) was prepared and characterized for flux and rejection performance using Gel Permeation Chromatography (GPC). Polyethylene glycol (PEG) and polyethylene oxide (PEO) with different molecular weights were used as the solutes. While using feed solution containing mixture of PEGs, higher rejection was observed than using individual PEG. The water flux of PBI-BuI membrane after passing individual PEG solutions showed considerable (similar to 36%) reduction, which could be attributable to the PEG adsorption on the membrane pore surface. PEG adsorption was further substantiated by SEM, IR and TGA. The amphoteric nature of PBI-BuI could cause H-bonding between membrane surface and PEG molecules, leading to PEG adsorption on the membrane and pore surface. To ascertain this postulation, a study with PAN-PSSALi (which does not contain H-bonding) based UF membrane containing negatively charged -SO3- group was done. It was found that PEG adsorption in this case is not as predominant as in earlier case. This membrane showed marginal reduction in water flux of 8%, vis-a-vis 36% reduction shown by PBI-BuI based membrane. This indicated that H-bonding present in PBI-BuI is mainly responsible for the PEG adsorption on its membrane and pore surface, in spite of PEG being a neutral molecule. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Gel permeation chromatography; Polybenzimidazole; Rejection; Solute adsorption; Ultrafiltration

Polybenzimidazole based polymeric ionic liquids (PILs): effects of controlled degree of N-quaternization on physical and gas permeation properties - Rewar, Anita S.; Bhavsar, Rupesh S.; Sreekumar, K.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric ionic liquids (PILs) are gaining increasing attention as potential membrane materials to be employed for CO2 separation. With a goal to improve gas permeability, this work presents a series of film forming PlLs obtained by controlled degree of N-quaternization (DQ) of PBI-BuI using a bulky 4-tertbutylbenzyl group. Concurrent effects of variation in ionic content and bulky group substitution were analyzed for physical and gas permeation properties of the resulting PILs. Attempted structural variations leading to simultaneous increments in ionic content and bulky groups offered amorphous polymers with acceptable thermal stability and non-monotonous chain packing density. Enhancement in pure gas permeability coupled with appreciable selectivity for various gas pairs was in accordance with the packing density variations in the series. Gas permeability showed maxima at DQ of just 13%. This conveyed that effects of bulky group substitution in retarding chain packing are overcome by attractive ionic interactions at much lower DQ in these PILs ionic interactions are thus more predominant in governing chain packing and gas permeation properties. These PILs possessed 3.3-20 times higher CO2 permeability in comparison to their parent PBI-BuI, without a significant loss in selectivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Degree of quaternization; Gas permeation; Polybenzimidazole; Polymeric ionic liquid

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)